Globalisation, populism, pandemics and the law the anarchy and the ecstasy - Findlay, Mark (Edward Elgar Publishing, 2021)
Advocating a style of law and a role for legal agency which returns to its essential humanist ideology and represents public spiritedness, this unique book confronts the myths surrounding globalisation, advancing the role for law as a change agent unburdened from its current market functionality. Mark Findlay argues that law has a new and urgent relevance to confront the absence of resilience in self-determined market places, and to make coherent the anarchic forces which are running, and ruining the world. The inevitability of law's re-invention during global crises is considered, offering a critical evaluation of the future of legal agency, service delivery and access to justice. Chapters also engage with citizen-centric surveillance society to examine the dangers to personal data, individual integrity, and work-life quality from unregulated mass data sharing. Exciting and thought-provoking, this book will be critical reading for scholars and students in law, economics and governance interested in globalisation and crises, such as pandemics, as well as populist politics and anxiety governance"--